Fenomena Split-Ticket Voting: Analisis Faktor Internal Pemilih pada Pemilu DPR RI–DPRD Provinsi - Muzakkir, Abd. Kahar; Bailusy, Ummi Suci Fathia (SIGn Journal of Social Science, 2023)
This research aims to analyze the phenomenon of split-ticket voting in the Central–Provincial House of Representatives election of 2019 in Makassar City based on internal voter factors. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that voters demonstrated a rational or strategic approach to ticket-splitting in the Central–Provincial House of Representatives election 2019 in Makassar City. Four significant internal factors influence this phenomenon. The strength of the partisanship factor indicates that voters tend to assess candidates for the Central–Provincial House of Representatives based on individual character and achievements rather than political party loyalty. Furthermore, incumbency information reveals voters’ pragmatic behavior based on rational choices to gain personal benefits. On the other hand, the strategic/policy balancing factor shows the significant influence of non-positional candidate characteristics in voter decisions. Finally, campaigns and socialization play a crucial role through strategic coordination among candidates for the Central–Provincial House of Representatives, political nodes, and voters, emphasizing the importance of narratives constructed through direct interactions and political gossip in securing voter support. Therefore, it is recommended that candidates for the Central–Provincial House of Representatives from the same political party enhance collaboration and coordination to create straight-ticket voting for their voters. Meanwhile, it is essential for political nodes to strengthen coordination that prioritizes transparency and integrity in conveying information. On the other hand, voters should be encouraged to actively seek information about candidates’ track records and policies to make decisions based more on substantial judgment than the influence of political gossip or short-term incentives. These steps are expected to reduce the phenomenon of split-ticket voting in the simultaneous elections for the coming period in Makassar City.